Challenges in the Reintegration of Disabled Individuals into the Workforce - Chikwe, Chidinma; Seyed Alitabar, Seyed Hadi; William , Erwin A.; Zadhasn, Zohreh (KMAN Counseling & Psychology Nexus, 2024)
The reintegration of disabled individuals into the workforce presents significant challenges and opportunities for enhancing workplace diversity and inclusivity. This study aims to explore the barriers and supports experienced by disabled workers as they navigate their return to employment, highlighting the complex interplay of personal, societal, and institutional factors that influence their reintegration process. This qualitative study utilized semi-structured interviews with 31 disabled individuals who have attempted to re-enter the workforce. Participants were selected through purposive sampling to capture a diverse range of disabilities, ages, and employment backgrounds. Data were analyzed using thematic analysis facilitated by NVivo software, focusing on reaching theoretical saturation where no new themes emerged from the data. Three main themes were identified: Employment Barriers, Support Systems, and Positive Experiences. Employment Barriers included categories such as Physical Accessibility, Social Attitudes, Workplace Policies, Technology and Tools, and Legal and Institutional barriers. Support Systems highlighted Government Programs, Community and Networks, Employer Support, and Personal Strategies. Positive Experiences encompassed Successful Accommodations, Employer Engagement, Career Development, and Advocacy and Awareness, illustrating facilitative aspects that aid reintegration. The study underscores the necessity of a multi-layered approach to the workforce reintegration of disabled individuals. Effective accommodations, proactive employer engagement, and robust support systems are crucial for overcoming the significant barriers these individuals face. Enhancing these areas can significantly improve employment outcomes for disabled workers, promoting a more inclusive and diverse workforce.